TINGKAT PARTISIPASI PEMILIH DENPASAR DALAM PILKADA 2018 - Widnyana, I Made Adi (VYAVAHARA DUTA, 2020)
Indonesia is a democratic country whose implementation is one of them is carried out through a democratic party called elections. Elections are held regularly in Indonesia which has been regulated by the rules and by the executors called the Electoral Commission. Elections in Indonesia are held to select formations in legislative and executive institutions both at the central and regional levels. Elections at the regional level are often referred to as elections, which are commonly used to select regional heads whether governors, regents, or mayors who are held in turn according to the stage of the period or time period. Elections in Bali after the reform period have been held several times, and it is always interesting to observe in addition to the election results, also related to the level of participation of its people as voters.Â The purpose of this study is to find out about the level of voter participation, especially in Denpasar at the 2018 election and the factors that affect the participation rate.From the results of the study it is known that the rate of voter registration in Denpasar city for the 2018 election is 63.18% that is in the moderate category. This lack of participation rate can be due to several factors, such as: economic factors of people who tend to vote to remain elected during the election process, factors that candidates or candidates feel are less attractive to them, or may be due to factors in voter data collection techniques. So it is advisable to overcome these factors can be done through the selection of the right election time or setting the election day as a holiday, in addition to socializing the mission vision of the candidate, as well as the systematic and measurable implementation of the stage so that no voter loses his or her voting rights due to technical factors.Keywords : Rate, Participation, Regional Elections, Medium, FactorsÂ